Pengaruh Teknologi Informasi Dan Pengetahuan Investasi Terhadap Minat Investasi Generasi Milenial Dengan Gender Sebagai Variabel Moderasi - Dessyana dessyana; Yola Yolanda (FIRM Journal of Management Studies, 2022)
This research aims to determine and analyze the effect of information technology and investment knowledgeon millennial generation’s investment interest with Gender as a moderating variable.The population in this research amounted to 958 students’s business faculty. The sampling method used was slovin method and obtained a sample of 399 students. The data analysis technique used is multiple linear regression analysis and regression analysis moderating variable with absolute difference value method.The results of the analysis shows that simultaneously and partially information technology and investment knowledgehave a significant effect on millennial generation’s investment interest. And gender is not able to moderate the relationship between information technology and investment knowledgeon millennial generation’s investment interest.